2007
DOI: 10.1186/1472-6963-7-21
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in radiological services: a nationwide survey

Abstract: Background: Geographical variation in health care services challenges the basic principle of fair allocation of health care resources. This study aimed to investigate geographical variation in the use of X-ray, CT, MRI and Ultrasound examinations in Norway, the contribution from public and private institutions, and the impact of accessibility and socioeconomic factors on variation in examination rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 21 publications
(27 reference statements)
6
44
0
Order By: Relevance
“…Similar results could be found in the literature. 6 Variability across Health Authorities and their district areas could depend on the over (under) use of specific examinations. Indeed, the one-way ANOVA analysis highlights that there is more variability between procedures (around 90% for MRI and 71% for CT) than within them (see table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results could be found in the literature. 6 Variability across Health Authorities and their district areas could depend on the over (under) use of specific examinations. Indeed, the one-way ANOVA analysis highlights that there is more variability between procedures (around 90% for MRI and 71% for CT) than within them (see table 2).…”
Section: Resultsmentioning
confidence: 99%
“…6 Bhargavan and Sunshine 11 highlighted great variability in the provision of DI services across areas and suggested that the use of appropriateness criteria, such as those defined by the American College of Radiology (ACR), may minimise these differences. Moreover, they explored this variability to highlight the state-level variables that affect it most, and they observed that the greater the number of Medicare providers, the greater the DI investigation rate per 1000 inhabitants.…”
Section: Tuscan Context and The Research Questionsmentioning
confidence: 99%
“…Another, not so immediate reason, was the unevenness between the distribution of imaging equipment that, in spite of availability and low operational costs, produces exams that require highly paid and trained radiologists to perform the analysis of the exam outcomes [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…Computed tomography (CT), X-ray imaging, magnetic resonance imaging (MRI ), fiber scope and ultra-sonic imaging are such techniques [1]. The purpose of these imaging methods is to visualize non-visible organ or tissue.…”
Section: Introductionmentioning
confidence: 98%